(3efGgL h WQb GdHMK GdYdejs - (3GHQGgje Hf YHO GdYRjR(B, (3GdOYjdLs ((3YeGf(B:s (3OGQ UaGA(B,s, 2009)
(3GdHMK GdYdej (B: (3WHjYJg , eaGgjeg , CgejJg , ahGFOg, eSejGJg , GdHMK GdYdej aj GdGSdGe ,COhGJ GdHMK GdYdej h GdJMdjd GdGMUGFj h GdGSJOdGdj h GdecJHI h GdHMK GdYdej h EYOGO hQbI GdHMK(B.s
(3eQGLY U(B.185s
Keywords: (3CSGdjH GdHMKs; (3GdHMK GdYdejs; (3GdJYdje GdYGdj(B- (3GdLGeYGJs; (3efGgL GdHMKs